Pemanfaatan Madu Sebagai Bahan Ekstender Untuk Kriopreservasi Sperma Ikan Gabus (Channa Striata) - Anugerah Al-Amin Mangkunegara; Sefti Heza Dwinanti; Mochamad Syaifudin (Jurnal Akuakultur Rawa Indonesia, 2019)
Cryopreservation of channa is needed to improve reproduction quality of seeds and broodstock. Some components are important for cryopreservation including quality and quantity of extender. The aim of this study was to investigate the influence honey as extender at different ratio on channa sperm cryopreservation quality. The research used response surface methodology (RSM) with three treatments (T); 300 mg. ml-1 (T1), 400 mg. ml-1 (T2), 500 mg. ml-1 (T3), which all treatments were replicated 3 times. The processed semen was equilibrated at 5°C for 3 h (chilling), packed into straws (0.25 ml), frozen and stored in a liquid nitrogen tank for 24 h before thawing and assessment of quality. Parameters observed were sperm characteristics such as (color, pH, concentration and sperm volume), motility and viability before and after cryopreservation. The results of this study indicated best treatment was honey concentration at 400 mg.ml-1 (T2). After 7 days preservation, the motility value was about 40 – 70 % (4 score), viability percentage was 64.15% and no abnormality was occurred on channa sperm.